Heteroestruturas magnéticas de NiFe2O4 e TiO2 para descontaminação fotocatalítica de arsênio em meio aquoso - Borges, Giulia Caroline de Cristo (2020)
Anthropogenic actions have been increasing the concentration of pollutants in water bodies, such as Arsenic (As) with toxic and carcinogenic potential, bringing with it the need to develop new forms of treatment for polluted bodies.Arsenic can be released into the environment through industrial waste, mining and pesticide use.Analternative that has been shown to be effective for waterand wastewater treatment are the Advanced Oxidative Processes (AOP's), amongwhich stands out the heterogeneous photocatalysis, which is based on the process of activation of a photocatalyst by radiation, generating hydroxyl radicals with high oxidizing power, being able to remove, from the aqueous medium, several organic and inorganic compounds. Titanium dioxide (TiO2) isthe most commonly used photocatalyst due to its intrinsic characteristics, however this semiconductor has limitations in use due to the fact that it is activated only by ultraviolet radiation (high band gap energy) and the difficulty of separating it from the reaction medium after photocatalytic tests. In order to overcome these limitations, TiO2can be associated with other semiconductors that reduce the band gap energy of the photocatalyst and facilitate its removal from the reaction medium after reactions.A class of magnetic compounds that contemplate these characteristics aretheferrites. In this context, the objective of this work was to synthesize photocatalysts containing a core of nickel ferrite (NiFe2O4) and a TiO2shell, forming the NiFe2O4@TiO2core shell structures for use in the decontamination of As (III) in aqueous medium. The photocatalysts were prepared by two methodologies (polymeric precursor method and co-precipitationof 8-hydroxyquinolinates) and calcined at three temperatures (500, 700 and 900 °C).The synthesized samples presented different crystalline phases: NiFe2O4, α-Fe2O3, NiO and the allotropic forms of TiO2(anatase and rutile).The sample prepared by co-precipitation and calcined at 900 °C still presented the Fe2TiO5phase. The samplesobtained by both methodologies presented particles formed by agglomerates ofgranules in which the NiFe2O4coating by TiO2 was not completely homogeneous. Some regions of the samples showed segregated NiFe2O4 and TiO2 particles. The estimated band gap values for all the samples were lower than those reportedin the literaturefor TiO2, which shows that the association of TiO2 with NiFe2O4 nanoparticles is an interesting strategy for reducing the TiO2 band gap value and consequently for the expansion of the energy absorption spectrum by the semiconductor.The sample synthesized by the polymeric precursor method and calcined at 700 °C showed the best performance in the photocatalytic oxidationof As (III) in aqueous media, resulting in the removal of 97.5% of the species after 80 min of reaction under visible radiation, which can be associated with the better coating of NiFe2O4particles by TiO2, higher nickel ferrite content in relation to theof α-Fe2O3and NiO simple oxides, the presence of both TiO2polymorphs (anatase and rutile) in considerable levels and lower band gap energy value.